Economic justice in Luke 19:1-10 : a post-apartheid imperial critical reading with reference to the land question in South Africa - Van Eck, Ernest (University of Pretoria, 2024)
Thesis (PhD (New Testament and Related Literature))--University of Pretoria, 2023.